Experimental infection of IS/885/00-like infectious bronchitis virus in specific pathogen free and commercial broiler chicks. (April 2016) - Awad, Faez; Chhabra, Rajesh; Forrester, Anne; Chantrey, Julian; Baylis, Matthew; Lemiere, Stephane; Hussein, Hussein Aly; Ganapathy, Kannan
Abstract: Pathogenesis of an IS/885/00-like (IS/885) strain of variant infectious bronchitis virus (IBV) was examined in one day old specific pathogen free (SPF) and commercial broiler chicks. Chicks were humanely euthanized at 3, 6, 9, 12, 15, 21 and 28 days post infection (dpi) for necropsy examination, and tissues were collected for histopathology and virus detection by reverse transcription polymerase chain reaction (RT-PCR). Respiratory clinical signs and gross lesions consisting of tracheal caseous exudate and plugs, and swollen kidneys (with or without) urate deposits were observed in SPF and broiler chicks. The onset of disease developed more slowly and were of lesser severity in broiler compared to SPF chicks, reflecting the inhibitory effects of the IBV maternal-antibodies in the broiler chicks or genetic/strain susceptibility, or both. Head swelling was observed in one infected broiler chick at 15 dpi and the virus was recovered by RT-PCR and isolation. In the IS/885-infected SPF chicks, cystic oviducts were found in two female chicks. IS/885 was isolated from the cystic fluid. Using ELISA, low to moderate levels of the antibodies to IBV was detected in the SPF compared to broiler infected chicks. Highlights: Pathogenesis of IBV IS/885 was examined in one day old SPF and broiler chicks. The virus caused respiratory distress, tracheal and kidney lesions in infected chicks. Head swelling was observed in one infected broiler chick at 15 dpi. Cystic oviducts were found in two female SPF chicks. IBV IS/885 examined in this study was pathogenic for both SPF and broiler chicks.